INTERNATIONAL CONVENTIONS AND AGREEMENTS IN THE ECOLOGICAL AREA - IN LIGHT OF MODERN CIVILIZATION AND INTERNATIONAL TRADE - Stanković, Milica S; Hafner, Petar (International Journal of Economic Practice and Policy, 2014)
A large number of authors examine the problem of environmental protection in their papers. The concept of sustainable development and intensive use of modern technology in order to overcome the environmental problems of modern civilization becomes an imperative. Theoretical engagement in ecological issues is not enough. It is necessary to implement ecological measures in practice and to spread environmental awareness. Modern science and social practice have interdependence of economy and ecology in their focus. The main direction of social change is movement from economic to ecological paradigm that involves an ethical responsibility to the current and future generations. There is a need to establish effective programs to protect the environment at the national and supranational level. Active international cooperation in the field of ecology has resulted in the formulation of a number of documents on environmental protection. This paper illustrates the importance of environmental protection and the necessity of implementing international conventions and agreements in the environmental field, with focus on their impact on international trade.
Keywords: environmental protection; ecology; international trade; international conventions and agreements; economic paradigm; ecological paradigm; sustainable development; World Trade Organization